Device preference and its influence on online reading strategies and reading struggles: a quantitative study among Malaysian undergraduates - Xavier Belaman, Jacinta Ann (Universiti Teknologi MARA, 2025)
This quantitative study investigates how Malaysian undergraduates’ preference for physical versus online reading materials relates to their online reading struggles and use of reading strategies. Using survey data from 200 students, the study examined group differences in reported reading struggles and in the use of global, problem-solving, and support strategies. Findings showed that students preferring print materials experienced significantly greater online reading challenges (moderate effect size) and relied more on support strategies, whereas students preferring digital texts more frequently used problem-solving strategies. Correlation analyses indicated that reading struggles were associated with different strategic responses depending on preference group, although differences in correlation strength were not statistically significant. These results suggest that reading preferences shape not only perceived difficulties but also the ways students adapt during online academic reading. The study highlights the need for tailored instructional support, especially within Malaysian ESL contexts, and recommends further mixed-methods research to deepen understanding of students’ online reading behaviours.